Politics Outside the "We": Foucault, Habermas, and the Foundations of Politics - King, Matthew A. (My University, 1998)
In this thesis, I attempt to rectify certain misunderstandings which typically have characterized contributions to the so-called HabermaslF oucault debate, and I propose a resolution to that debate. First, I clarify what I call "the Habermasian challenge" to Foucault--that is, Habermas's contention that Foucault must provide an account of the "normative foundations" of his political criticism, but, at the same time, that no such account can be consistent with Foucault's genealogical work--and show why attempts to answer that challenge on Foucault's behalf are unsuccessful. Second, I elaborate Habermas's own purported normative foundations--his "discourse ethics"--and I show why they cannot function in the way that they must for his challenge to Foucault to retain its point. Third, I argue that Foucault must reject foundationalism because foundationalism is incompatible with his ethics: both with his philosophical ethic of "parrhesia", and with his political ethic as someone identifying with those outside what I call the "central 'we'" of the society of which he is a member.
Keywords: Philosophy; Philosophy